2015
DOI: 10.12738/estp.2015.6.0156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Creative Drama on Academic Achievement: A Meta-analytic and Thematic Analysis

Abstract: The aim of this study was to determine the effect of creative drama on achievement through the use of quantitative and qualitative research methods. In the quantitative section of the research, the meta-analytic method was used and an attempt was made to include all studies of creative drama carried out between 2000 and 2014 at the national and international levels. As a result, 40 studies (8 articles, 28 Mas, and 4 PhD theses) complied with the inclusion criteria, which consisted of examining the effect of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
1
17
0
3
Order By: Relevance
“…In the literature, there are meta-analysis studies exploring the effect of the creative drama method on students' academic achievement (Akdemir & Karakus, 2016;Aydin, Kasarci & Yurt, 2012;Batdi & Batdi, 2015;Bicer, 2017;Canturk Gunhan, 2016;Lee, Patall, Cawthon, & Steingut, 2015;Ulubey & Toraman, 2015) and attitudes towards different courses (Toraman & Ulubey, 2016). In these studies, it was concluded that the creative drama method is effective in these respects.…”
Section: Introductiomentioning
confidence: 99%
“…In the literature, there are meta-analysis studies exploring the effect of the creative drama method on students' academic achievement (Akdemir & Karakus, 2016;Aydin, Kasarci & Yurt, 2012;Batdi & Batdi, 2015;Bicer, 2017;Canturk Gunhan, 2016;Lee, Patall, Cawthon, & Steingut, 2015;Ulubey & Toraman, 2015) and attitudes towards different courses (Toraman & Ulubey, 2016). In these studies, it was concluded that the creative drama method is effective in these respects.…”
Section: Introductiomentioning
confidence: 99%
“…However, [58] determined that creative drama-based learning did not affect the success of students to an extent which yields a significant difference as compared to the conventional teaching method. It is also observed in the meta-analyses examining the relation of creative drama-based learning to other disciplines [5]; [47]; [67] that this method positively affects student success as compared to conventional teaching method.…”
Section: Resultsmentioning
confidence: 94%
“…Details on the methods, publication type, date of publication, subject of publication and educational level of studies examined in scope of the research are given in Studies included in the meta-analysis employed the methods of multiple intelligences based learning (5), creative drama based learning (6), collaborative learning (6) and game-based learning (5). In respect to the types of publication, the majority of the studies were comprised of master's degree theses (11) and the studies were distributed among different years of publication, and as for subject of publication, various language skills were addressed in a mixed manner whereas in respect to educational level, the studies were mostly focused on primary education level (17).…”
Section: Criteria For Inclusionmentioning
confidence: 99%
“…Bu araştırmayla, yazma becerisinin etkili bir biçimde ortaya çıkarılmasında yaratıcı dramanın kullanılması, daha önce yapılan çalışmalarda olduğu gibi (Ataman, 2006;Erkan ve Aykaç, 2014;Sevim ve Özdemir Erem, 2013;Susar Kırmızı, 2009), öğrencilerin yazılarını oluşturan iç yapı, dış yapı, dil ve anlatım gibi süreçleri daha iyi yapılandırmalarına olanak sağlamıştır. Çünkü yaratıcı drama, içinde taşıdığı etkin katılım, doğaçlama, rol oynama, kendiliğindenlik, farkındalık, -mış gibi yapma, duyarlılık, değerlendirme, düzeltme, izleme gibi oyunsu ve üst düzey düşünme süreçleriyle çocuğu kendine güvenen, başarılı ve becerilerini geliştirme sorumluluğu alan bir katılımcıya dönüştürebilir (Adıgüzel ve Timuçin, 2010;Aldavero, 2008;Annarella, 1999;Atish, 2015;Batdı ve Batdı, 2015;Conard ve Asher, 2000;Ernst-Slavit ve Wenger, 1998;Freeman, Sullivan ve Fulton, 2003;Gallagher, 1997;Kaf, 1999;Önalan Akfırat, 2006;Öztürk, 2001;Wagner, 1988). Çünkü duygu ve düşüncelerini bu süreçlerin katkısıyla etkili bir biçimde yazıya döken öğrencilerin akademik başarıları daha çok gelişmektedir (Atish, 2015;Erkan ve Aykaç, 2014;Joseph, 2014;Kaf, 1999;Susar Kırmızı, 2009;Timothy ve Apata, 2014).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Yaratıcı dramanın öğrencilerin akademik başarısını geliştirdiğine yönelik birçok çalışma bulunmaktadır (Almaz, İşeri ve Ünal, 2014;Aydeniz ve Özçelik, 2012;Atish, 2015;Batdı ve Batdı, 2015;Gencel, 2009;Joseph, 2014;Kaf, 1999;Oğur ve Kılıç, 2005;Sarıçoban, 2004;Selmanoğlu, 2009;Taşkın Can, 2013;Timothy ve Apata, 2014). Özellikle yazma becerisinin gelişimi yönündeki alanyazın incelendiğinde, yaratıcı drama yöntemine dayalı etkinliklerin yazmaya yönelik tutumu olumlu yönde etkilediği görülmektedir (Susar Kırmızı, 2009).…”
Section: Introductionunclassified